Interview with Nadine Bowers Du Toit - M. Laubscher (Acta Theologica)
Nadine Bowers Du Toit is a professor in the Department of Practical Theology and Missiology at the Faculty of Theology at the University of Stellenbosch. She holds a PhD in Practical Theology (Theology and Development) and her research over the past 20 years has focused on the role of faith communities in addressing the intersecting issues of race, inequality, gender and poverty. Her most recent projects have been funded by grants from the National Research Foundation and the Nagel Centre for World Christianity. Besides lecturing, publishing and supervising postgraduate students, Nadine is often invited to address congregations, church leaders and faith-based organisations on topics pertaining to social justice. She sees herself as an “activist academic”, always advocating for more diverse voices to be heard: to this end, she chairs the transformation committee in the Faculty of Theology. Nadine is the director of the Unit for Religion and Development and serves on the boards of several non-governmental organisations. She is the current vice-president of the International Academy of Practical Theology.